The development and evaluation of a Nd:YAG laser incorporating an unstable resonator - De Kock, Trevor Neil (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1986)
Introduction: For approximately the last eight years the Laser Section of the National Physical Research Laboratory (NPRL) has been interested in inter alia, pulsed solid-state lasers and in particular, Nd:YAG. Investigations of various resonator types were undertaken with a view to the improvement of the laser parameters such as output energy, pulse width, beam quality and sensitivity to mirror misalignment. In 1980 a Nd: YAG laser employing a rotating prism Q-switch was constructed (Preussler (1980)). It involves rotating one of the two cavity reflectors so that they are parallel for only a brief instant in time. Typically the prism must rotate at a speed of 20 000 r.p.m. to ensure a single pulse output. Such lasers suffer from the tendency to emit multiple pulses, they are very noisy and they require frequent maintenance because of the short lifetime of the bearings. A resonator employing conventional curved mirrors and an electro-optical Q-switch was constructed in 1980 (Robertson & Preussler (1982)). In 1981 an electro-optically Q-swi tched laser making use of a crossed Porro-prism resonator was investigated due to its relative insensitivity to misalignment of the reflectors compared with the conventional mirror resonator (Nortier (1981)). Improvements in terms of output power, beam divergence and beam quality can be achieved by making use of a so-called unstable resonator. Such a laser has been investigated and is reported on in this study. Chapter 2 provides some background into laser theory and operation while chapter 3 deals with the theory of the unstable resonator. Chapter 4 provides details of the experimental equipment and techniques used in the work and chapter 5 discusses the evaluation of the project and results obtained.
Keywords: Nd-YAG lasers; Lasers -- Resonators; Laser beams